2019
DOI: 10.3389/fpsyg.2018.02695
|View full text |Cite
|
Sign up to set email alerts
|

Combine Your “Will” and “Able”: Career Adaptability’s Influence on Performance

Abstract: Adaptivity and adaptability are two key elements representing one’s “willingness” and “ability,” respectively, in the career construction theory (CCT) framework. On the basis of CCT and complemented by the visual of resources in the conservation of resources theory, this study combines career issues and performance and examines the joint effect of adaptivity and adaptability on career self-management which will lead to improved performance. Using a sample of Chinese employees (N = 232), the study first examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Career construction requires career adaptability, meaning being ready to cope with uncertainties from unpredictable shifts in their job and working conditions ( Savickas, 1997 ). Many studies have argued the antecedents and consequences of career adaptability in predicting positive career-related outcomes ( Jiang, 2017 ; Zhuang et al, 2018 ; Gao et al, 2019 ; Ayala et al, 2020 ; Mei et al, 2021 ; Wang et al, 2021 ). As Obschonka et al (2018) have indicated career adaptability is important in responding to the uncertain environment in one’s occupational development.…”
Section: Career Construction Theorymentioning
confidence: 99%
“…Career construction requires career adaptability, meaning being ready to cope with uncertainties from unpredictable shifts in their job and working conditions ( Savickas, 1997 ). Many studies have argued the antecedents and consequences of career adaptability in predicting positive career-related outcomes ( Jiang, 2017 ; Zhuang et al, 2018 ; Gao et al, 2019 ; Ayala et al, 2020 ; Mei et al, 2021 ; Wang et al, 2021 ). As Obschonka et al (2018) have indicated career adaptability is important in responding to the uncertain environment in one’s occupational development.…”
Section: Career Construction Theorymentioning
confidence: 99%
“…As such, more than developing technical skills, it is essential to also develop a wide range of soft skills which add value when starting one’s professional career [ 7 ]. Particularly, in order for university students to be prepared for the challenges that the labor market offers them, it is essential that they know what is expected of them, namely which skills are employers looking for [ 37 ]. With this knowledge these individuals, when looking for their first job, become able to know which roles to adopt, how to manage conflicts, how to coordinate their work and carry out it in a more cooperative and integrated way with peers, superiors and clients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although resilience is not amongst the ten most-valued skills in Gabor et al [ 36 ], 42.0% of the employers mentioned it, suggesting that the ability to overcome obstacles and frustrations seems to be highly relevant in the organizational context, particularly regarding career development and management. Furthermore, the job market values people who can easily adapt to new contexts and know how to uphold a positive outlook, because—aside from influencing colleagues with their energy, joy and enthusiasm—those persons seem to be more productive and determined when pursuing a goal [ 37 ]. Also, organizations want professionals who are able to understand and solve problems efficiently, effectively and promptly, which shows that time management is another key competence needed for achieving professional success [ 38 ].…”
Section: Skillsmentioning
confidence: 99%
“…Career adaptability has a significant impact on career development and work-and life-related variables. For example, career adaptability can promote the successful career transition of individuals (Brown et al, 2012;Guan et al, 2015b); positively predicts performance, with this relationship partially mediated by career self-management (Gao et al, 2019); and improve individuals' satisfaction with their work and life (Zacher and Hannes, 2014;Xie et al, 2016), as well as their well-being (Maggiori et al, 2013;Hartung and Taber, 2008) and job performance. It is serves as an important predictor for indicators of well-being, such as life satisfaction (Rudolph et al, 2017); it is positively correlated with the academic achievement of adolescents (Negru-Subtirica and Pop, 2016); it is related to the job content plateau (Jiang, 2016); it can reduce the anxiety, feelings of failure (Pouyaud et al, 2012), and work stress (Nilforooshan and Salimi, 2016) of individuals; and it plays an intermediary role between proactive personality and internal professional growth (Hu and Cheng, 2017).…”
Section: Introductionmentioning
confidence: 99%